2010
DOI: 10.2164/jandrol.110.010348
|View full text |Cite
|
Sign up to set email alerts
|

Association of Paraoxonase Gene Polymorphisms With Sperm Parameters

Abstract: Paraoxonase (PON) is a high-density lipoproteinassociated enzyme that prevents low-density lipoprotein oxidation. PON proteins, localized in the seminiferous tubules and in spermatozoa, have been implicated in the pathogenesis of male infertility. In the present study, we sought to explore the contribution of the PON gene variants to sperm parameters. One hundred twenty oligospermic and 170 normozoospermic men were examined during infertility investigation. DNA was extracted from spermatozoa, and the PON1(L/M)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…In accordance with this finding, it has been reported that normozoospermic men with the PON1 192Q allele have higher sperm motility than carriers of the R allele [Lazaros et al 2011]. It is reported that the PON1 192 R allele carriers have lower PON1 activity and higher lipid peroxidation compared with Q allele carriers, which may explain the effect of various PON1 genotypes on sperm parameters [Costa et al 2003;Mackness et al 1998b].…”
Section: Pon1 Genotypessupporting
confidence: 58%
See 4 more Smart Citations
“…In accordance with this finding, it has been reported that normozoospermic men with the PON1 192Q allele have higher sperm motility than carriers of the R allele [Lazaros et al 2011]. It is reported that the PON1 192 R allele carriers have lower PON1 activity and higher lipid peroxidation compared with Q allele carriers, which may explain the effect of various PON1 genotypes on sperm parameters [Costa et al 2003;Mackness et al 1998b].…”
Section: Pon1 Genotypessupporting
confidence: 58%
“…Some studies have investigated the possible roles of this enzyme and its polymorphisms in male infertility [Corbo et al 2008;Volk et al 2011;Lazaros et al 2011]. In this study, we have examined the PON1 Q192R polymorphism (glutamine is replaced by arginine), plasma Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations